The use of stem cells in aesthetic dermatology and plastic surgery procedures. A compact review of experimental and clinical applications - Nowacki, Maciej; Kloskowski, Tomasz; Pietkun, Katarzyna; Zegarski, Maciej; Pokrywczyńska, Marta; Habib, Samy L.; Drewa, Tomasz; Zegarska, Barbara (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
The aim of this paper was to collect currently available data related to the use of stem cells in aesthetic dermatology and plastic surgery based on a systemic review of experimental and clinical applications. We found that the use of stem cells is very promising but the current state of art is still not effective. This situation is connected with not fully known mechanisms of cell interactions, possible risks and side effects. We think that there is a big need to create and conduct different studies which could resolve problems of stem cells use for implementation into aesthetic dermatology and plastic surgery.